Occurrence of dental involvement in victims of violence - Barbieri, Ana Amélia; França, Cristiano de; Naressi, Suely Carvalho Mutti; Tosello, Darcy de Oliveira; Daruge Júnior, Eduardo (Brazilian Dental Science, 2017)
Objective - To verify the occurrence of dental involvement described in medical examination reports on facial trauma resulting from interpersonal violence. Material and methods: an observational, analytical, and retrospective study that verified the dental involvement described in all the medical examination reports involving facial trauma, arising from interpersonal violence, issued by the Instituto Médico Legal - IML (Forensic Medicine Institute) of Taubaté, in São Paulo state, in a period of 24 months, considering gender and age group. Results: Of the 12,184 reports issued during the period studied, 1,971 (16.17%) described facial injuries resulting from aggression, and of these, 5.07% contained reports of dental involvement. The most frequent injury was a fracture (2.99%), in the age range between 16 and 24 years (31.42%), and the gender, male (56%). Conclusion: The facial injuries resulting from interpersonal violence in the analyzed period amounted to 16.17% of the total of cases, with 5.07% of these presenting reports of dental involvement. KEYWORDS Forensic Dentistry; Injuries; Violence.